PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP TINGKAT LOYALITAS PELANGGAN - HERMANTO; ANGEL PURWANTI (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2020)
Interpersonal communication is very important in a business organization because it has a significant influence on customer loyalty. The purpose of this studt is look at the effect of interpersonal communication on customer loyalty in CV. Putra Jayar Service on Batam City. The method used in this research is quantitative with simple linear regression analysis using IBM SPSS Statistics 23 application. Samples on this research were 276 respondents by random sampling method. The results showed that t count (6.282) > t table (1.645) with significance level 0.000 < 0.05 that indicates interpersonal communication significantly influence customer loyalty. Coefficient of R Square is 0.275 which shows that interpersonal communication variable have effective contribution of 27.5% to customer loyalty and the remaining 72.5% customer loyalty influenced by variables not examined in this study.